Characterization of patients operated due to external abdominal hernias in a Venezuelan diagnosis center - Ramiro Julio Bejerano García (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive, prospective and cross-sectional study of the 747 operated patients due to external abdominal hernias in "La Atlántida" Comprehensive Diagnosis Center from Vargas State, of the Bolivarian Republic of Venezuela was carried out from April, 2013 to December, 2017 with the objective of characterizing them according to variables of interest for the investigation. In the series the male sex (75.1 %), the age group 51-60 years (37.8 %), the hypertension as the main comorbidity (32.0 %), the inguinal hernia as the most frequent variety (63.7 %), besides the repair with prosthesis without tension (mesh) as the most used procedure and without hernia relapse (72.6 %) prevailed; also, the complications were within the accepted international range (5.1 %) and the edema of the cord turned out to be the most common.